The importance of the development of domestic tourism for the country's economy - Tleuberdinova, А.Т.; Shaуekina, Zh.M.; Salauatova, D.M.; Torzhanova, D.A. (BUKETOV BUSINESS REVIEW, 2017)
In the article features and problems of development of domestic tourism in the Republic of Kazakhstan are considered. The authors have studied the experience of developing domestic tourism in foreign countries, analyzed statistical data, identified various characteristics of the domestic tourism market, studied the factors underlying the weaknesses of this market. The authors analyzed the main advantages of developing the domestic tourism market and considered the most promising types of domestic tourism for development in Kazakhstan. Particular attention was paid to the development of transport infrastructure, in particular, railways and air traffic and its role in the development of domestic tourism. In the article the authors analyzed the main motives for travels of both domestic tourists and international travelers. The authors gave suggestions on increasing the level of development of the domestic market.The authors consider the opportunities for developing family, event and other promising types of tourism.